Synthesis of Mannich Bases of 8-Hydroxyquinoline - Humaira Siddiqi; Shaheen Faizi; Shaista Naz; Erum Zahir (Journal of Basic & Applied Sciences, 2015)
In search of new potential therapeutic agents, 8-Hydroxyquinoline which is a highly active antifungal and antibacterial agent was subjected to Mannich reaction. Different combinations of aromatic aldehyde and aromatic amines were used for Mannich reaction on 8-Hydroxyquinoline from which one new 7-[α-(anilino)-3’,4’-dimethoxybenzyl]-8-hydroxyquinoline (3) and two known Mannich bases (1,2) were obtained.